Phylogeny and expression patterns of ERF genes that are potential reproductive inducers in hybrid larch - Junfei Hao; Daixi Xu; Chen Wang; Qing Cao; Qingrong Zhao; Miaomiao Xie; Hanguo Zhang; Lei Zhang (BMC Genomics, 2024)
Abstract Background Larch is an important component of northern forests and a major cultivated tree species in restoration of forest cover using improved seed material. In recent years, the continuous low seed production has severely affected the production of improved variety seedlings and natural regeneration. However, research on the reproductive growth of gymnosperms is extremely scarce. Results In this study, based on differential transcriptome analysis of two asexual reproductive phases, namely high-yield and low-yield, we further screened 5 ERF family genes that may affect the reproductive development of larch. We analyzed their genetic relationships and predicted their physicochemical properties. The expression patterns of these genes were analyzed in different tissues, developmental stages, hormone treatments, and environmental conditions in hybrid larch. Conclusion The results showed that all 5 genes were induced by low temperature and ABA, and their expression patterns in different tissues suggested a suppressive role in the development of female cones in larch. Among them, LkoERF3-like1 and LkoERF071 may be involved in the flowering age pathway. This study enriches the scarce research on reproductive development in gymnosperms and provides a theoretical basis and research direction for regulating the reproductive development of larch in seed orchards.